2017
DOI: 10.4236/jss.2017.511014
|View full text |Cite
|
Sign up to set email alerts
|

Suicide for the Purpose of Gaining Insurance Payouts in Japan

Abstract: Purpose: Studies on suicide for the purpose of gaining insurance payouts are rare globally; analyses of this phenomenon can help us understand it better and achieve more individualized care and support. Method: We used suicide data for the period from 2007 to 2015 from the "Summary Document Concerned with Suicide" released by the Japanese National Police Agency. We organized data on suicide committed to gain insurance payouts according to sex, age group, and year. We compared the sex ratio between these cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast, a retrospective evaluation of life insurance contracts held by 468 persons who died by suicide within the suicide exclusion period described in German policies found that only a few persons acquired their insurance for financial advantage for their relatives and concluded that the 3-year exclusion clause was "an effective barrier against misuse." 24 However, only a single study in the literature, published by Kodama et al, 25 has specifically examined these financial strains as motivational correlates of suicides for the purpose of gaining "insurance payouts," finding less than one half of 1% of suicides in Japan to be so motivated.…”
Section: Discouraging Fraudmentioning
confidence: 99%
“…In contrast, a retrospective evaluation of life insurance contracts held by 468 persons who died by suicide within the suicide exclusion period described in German policies found that only a few persons acquired their insurance for financial advantage for their relatives and concluded that the 3-year exclusion clause was "an effective barrier against misuse." 24 However, only a single study in the literature, published by Kodama et al, 25 has specifically examined these financial strains as motivational correlates of suicides for the purpose of gaining "insurance payouts," finding less than one half of 1% of suicides in Japan to be so motivated.…”
Section: Discouraging Fraudmentioning
confidence: 99%
“…Insurance company regulations in Japan then stipulated that customers could take the policy after several years of signing the contract. In the early time insurance was introduced, Japanese people registered in droves, and after signing the contract, some of them committed suicide to immediately get a policy (Kodama, Fujimoto, Tamura, & Kataoka, 2017). Seeing that insurance policies are used, the family's financial condition also influences the child to commit suicide.…”
Section: Broken Family and Difficultiesmentioning
confidence: 99%